SUBSTITUSI TEPUNG TERIGU DENGAN TEPUNG BERAS DALAM PEMBUTAN KUE BOLU (BHOI), PENGANAN TRADISONAL ACEH, DI KECAMATAN MEURAXA - Wardiah, Wardiah (Universitas Muhammadiyah Aceh, 2010)
To keep bhoi exist, we try to just rice flour as the main material in making process. Based on the above statement, this experiment is purpose to (1) Know how many percent of using rice flour can replace wheat flour, (2) Know the taste comparison between bhoi with is made from rice flour to bhoi which is made from wheat flour, (3) Know the texture comparison between bhoi with is made from rice to bhoi which is made from wheat flour. This experiment is conducted in Lambung village Meuraxa sub-district, Banda Aceh district and also in Tata Boga’s Laboratory. Research setting which used is Complete Random Plan system non factorial which consists of six treatment of using rice flour to replace wheat flour in mixing material to make bhoi by composition of rice flour 0%,20%, 40%, 60%, 80%,and 100%. This research is repeated six times through each treatment. There are five informants whose have knowledge and skill in making bhoi and also ten prominent figure woman whose know and ever make bhoi. The experiment is conducted to texture and taste which is examined by ten panelists to the hedonic and acceptability test. From the data can be concluded thah (1) Rice flour can replace wheat flour 0%,20%, 40%, 60%, 80%,and 100%. The most panelist like is the treatment of making bhoi by adding 0% and 100% rice flour, (2) It gives and abvious effect of using rice flour to the taste of bhoi and panelists be fond of the taste at 100% treatment, (3) It gives an obvious effect of using rice flour to the texture of bhoi at 0% and 100% treatment which the most panelists like. Keywords: Bhoi, Aceh’s traditional cake, wheat flour, rice flour. DAFTAR PUSTAKA Arikunto. S (1991). Prosedur Penelitian. PT Rineka Cipta, Jakarta. Depdikbud (1983). Kamus Besar Bahasa Indonesia. Balai Pustaka. Jakarta Depdikbud, Kamus Aceh Indonesia 1. Pemahaman dan Pengembangan Bahasa. Hanafiah, K, A. (1993). Rancangan Percobaan Teori Aplikasi. Fakultas Pertanian Universitas Sriwijaya. Palembang. Hasan, Ibrahim. (1984). Prospek Penganan Tradisional Aceh dalam Dimensi Ekonomi. Jakarta: Kantor Menteri Negara Urusan Pangan, Budaya Logistik. Hoesin, M. (1970). Adat Atjeh. Dinas Pendidikan dan Kebudayaan Propinsi Daerah Istimewa Aceh. Hogronge, S, (1985), Aceh di Mata Koloniolis. Yayasan Suho Gurun, Jakarta. Lawrani, M (1991) Budidaya dan Penganan Pasca Panen. Kanisius Rahayu, W. P (1998). Penilaian Organopleptik IPB, Bogor. Sarifah, L, (1984). Pengetahuan dan Penyajian MakananIndonesia. PT Gramedia, Jakarta. Soekarto, Soewarno T (1981) Penilaian Organopleptil. IPB US Wheat Associates. (1983), Pedoman Pembuatan Rod dan Kue. Djambatan.